Suture Fixation of a Pediatric Pelvic Ring Injury: A Case Report. Issue 4 (October 2021) - LaTulip, Scott M.; DiCenso, Stefano M.; Romeo, Nicholas M.; Mistovich, R. Justin
Abstract : Case: A 2-year-old male child presented as a polytrauma after having been run over by a motor vehicle. His orthopaedic injuries included a pelvic ring injury, a displaced subtrochanteric femur fracture, and a clavicle fracture. His pelvic ring injury ultimately required open reduction with suture fixation after failure of closed management. Conclusion: Pelvic ring injuries are relatively uncommon in young children, and even more rarely do they require surgical intervention. We detail the case of one such patient who required open management of his anteroposterior compression II pelvic ring injury, and we describe an alternative fixation technique using suture wire.